Microplastics in the Waters of European Lakes and Their Potential Effect on Food Webs: a Review - Bowszys, Magdalena (Polish Journal of Natural Sciences, 2023)
Microplastics are widely distributed in aquatic environments. Studies to date have focused mainly on marine environments, and there is a substantial body of work in this topic. Contamination in freshwater ecosystems is a new and growing problem that has received decidedly less attention; this includes lakes that are particularly vulnerable because of their close proximity to emission sources. The first studies on the problem of lake microplastic pollution were not published until 2011, but interest among researchers has increased in recent years. The aim of this review is to assess the current state of knowledge about levels of microplastic pollution in European lake waters and to identify the most urgent areas of research that are required. A review of available data indicated that the number of lakes that have been investigated remains small in light of the overall number of lakes in Europe. There is a near total lack of data on the topic of the pollution of microplastics < 300 µm. Similarly, little attention is paid to the fate of microplastics in the water column and the influence they have on lake food webs. Furthermore, there is also a near total lack of multi-dimensional models that would describe the primary factors responsible for the accumulation of microplastics in lakes.